Satisfaction of users of copper intrauterine device: Analysis of patients at the family planning outpatium of a public hospital - Braga, Évelyn Mayara Rocha; Paiva, Daniele Socorro de Brito Souza (Seven Editora, 2023)
Introduction: In Brazil, the guarantee to contraception is given through the National Family Planning Policy of 2007, which offers several free contraceptive methods, among them the copper intrauterine device (IUD), a highly effective contraceptive method. Objectives: To know the satisfaction of users with the IUD and specifically to evaluate and identify the interference of side effects in the quality of life of patients. Methods: This is a prospective, field-cross-sectional study with a quantitative approach, using a structured questionnaire applied to copper IUD users, inserted in the service and with at least 03 months of use. Results: The users were satisfied with the copper IUD (92.6%) and did not report discomfort with the method (59.5%), although 63.0%, 77.8% and 44.5% presented abdominal pain (outside the menstrual period), menstrual colic and increased menstrual flow, respectively. Conclusion: Most users were satisfied with the copper IUD, continuing its use, despite the existence of some side effects. The study demonstrated that the IUD is an excellent contraceptive alternative for being effective, having a prolonged action, reduced cost and with good satisfaction among users. DOI:https://doi.org/10.56238/ptoketheeducati-052